Analiza zmian w rozliczeniach finansowych pomiędzy firmami z siedzibami w różnych państwach na przykładzie przedsiębiorstw województwa podkarpackiego - Sieńko, Barbara; Stokłosa, Krzesław (The Analysis of Changes in Financial Settlements Between Enterprises with Offices in Deferent Countries - an Example of Enterprises from Podkarpackie Region, 2006)
One of the essential conditions of development and increasing of podkarpackie region competitiveness, in context of Poland's membership in EU, as well as process of globalization, is efficient financial infrastructure. The description analyzes changing in financial setting of podkarpacie region enterprises with enterprises seats out of Poland, during 2004 year; whit was the first year Polish membership in European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 586-592